Nasolabial angle in finger sucking patients - Mayury Kuramae; Ivana Uglik Garbui; Maria Beatriz Borges de Araujo Magnani; João Sarmento Pereira Neto; Gláucia Maria Bovi Ambrosano (Universidade Estadual de Campinas, 2015)
The purpose of this study is to analise the nasolabial angle and other cephalometric measurements that express the anteroposterior relationship of maxilla and mandibule in individuals with finger sucking habit. Thirty lateral cephalograms were selected from the patient files of the scientific documentation service, Orthodontic Graduation Course of the Piracicaba College of Dentistry, FOP/UNICAMP. The selection criteria was white Brazilian female subjects, 7 to 10 years old, in the phase of mixed dentition, and presenting finger sucking habit. The observed cephalometric measurements were: nasolabial angle, SNA, SNB, ANB, 1.NA, 1-NA and Nperp-A. The results were compared using Student's 't' test and, significance level of 5% (á = 0,05). The analysis showed no differences in the nasolabial angle in subjects presenting finger sucking habit; the maxilla and mandibule was well positioned, relative to the cranial base, and the upper incisors were well positioned.